Kepatuhan Wajib Pajak dalam Perspektif Gender: Peran Sikap dan Kebijakan Internal - Kevry Ramdany; Aries Tanno (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2026)
Taxpayer compliance plays an important role in supporting government revenue derived from taxation. However, the level of taxpayer compliance continues to vary due to individual behavioral factors and organizational policy mechanisms. This research seeks to analyze the influence of taxpayer attitudes and internal organizational policies on taxpayer compliance while also exploring gender as a moderating variable in these relationships. In this study, internal organizational policy is operationalized as an internal remuneration withholding policy, whereby employee remuneration is temporarily withheld when tax reporting obligations have not been fulfilled. This study utilized a quantitative research approach by conducting a survey among hospital employees in Padang City. Data collection was carried out using questionnaires, which were administered to participants chosen through a purposive sampling method. The data were analyzed using variance-based Structural Equation Modeling with WarpPLS software to evaluate the structural relationships among variables. The results indicate that the internal remuneration withholding policy has a positive and stronger effect on promoting taxpayer compliance. Taxpayer attitudes also positively influence taxpayer compliance. However, gender does not significantly moderate the relationship between the independent variables and taxpayer compliance. These findings suggest that firm organizational control policies, particularly remuneration withholding mechanisms, can serve as effective instruments for enhancing taxpayer compliance alongside the development of positive taxpayer attitudes.